Festes a Alzira en 1710 per les victòries de Felip V. Una mostra d’adhesió a la causa borbònica en la guerra de Successió. - Olivares Torres, Enric (Scripta, 2022)
The celebration of a feast of thanksgiving for the victories of Brihuega and Villaviciosa at the end of 1710 was the ideal setting for the exhibition of sincere signs of loyalty to the monarch by the town of Alzira. The purpose of these displays of joy through the feast, literature and visuality had as its main objective the transmission of a series of values and trustworthiness towards the monarchical power while legitimizing before its vassals the adhesion of the town to Bourbon in a crucial moment when the throne of Spain was decided definitely toward its position in the last moments of the War of Succession.